An In Vivo Rat Study of Bioresorbable Mg-2Zn-2Ga Alloy Implants - Alexey Drobyshev; Zaira Gurganchova; Nikolay Redko; Alexander Komissarov; Viacheslav Bazhenov; Eugene S. Statnik; Iuliia A. Sadykova; Eugeny Sviridov; Alexey I. Salimon; Alexander M. Korsunsky; Oleg Zayratyants; Denis Ushmarov; et al. (Bioengineering, 2023)
In the present study, pins made from the novel Mg-2Zn-2Ga alloy were installed within the femoral bones of six Wistar rats. The level of bioresorption was assessed after 1, 3, and 6 months by radiography, histology, SEM, and EDX. Significant bioresorption was evident after 3 months, and complete dissolution of the pins occurred at 6 months after the installation. No pronounced gas cavities could be found at the pin installation sites throughout the postoperative period. The animals’ blood parameters showed no signs of inflammation or toxication. These findings are sufficiently encouraging to motivate further research to broaden the experimental coverage to increase the number of observed animals and to conduct tests involving other, larger animals.